AKREDITASI TERHADAP KINERJA PENDIDIK DAN HASIL UJIAN NASIONAL MADRASAH - FIRDAUS BASUNI (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2011)
Many efforts have been done by the government to improve the quality of education and one of them is accreditation program. This research is focused to identify the impact of accreditation on teachers’ performance and national examination score of Madrasah. The research used an ex post facto method to analyze past events and their time order to find out the influencing factors. The population of this study was 8.844 madrasah located in provinces of DKI Jakarta, Central Java, South Sulawesi, and South Sumatera. Using purposive sampling technique, 202 teachers from 73 madrasah representing those from the provinces mentioned were taken as the samples. Data analysis and interpretation suggest that: (1) From accreditation status point of view, there was no significant difference between teachers’ performances of accredited madrasah and those from non-accredited ones, (2) There was a significant difference between the teachers’ performance judging from the accreditation level point of view (on the scale of A, B, C, or D), between the teachers’ performance of madrasahs with A accreditation and B accreditation; and between the teachers’ performance of madrasah with A accreditation and C accreditation, (3) There was no significant differences between the teachers’ performance of madrasah with B accreditation and C accreditation, (4) there was a significant difference between the national examination score of accredited madrasah and the non-accreditation ones, and (5) There was no significant difference between national examination score of madrasahs with different accreditation scale of level (A, B, C, or D). Shortly, the accreditation has more influence on the teachers’ performances than on the national examination scores.